New Diazo Coupling Reactions for Visible Spectrophotometric Determination of Alfuzosin in Pharmaceutical Preparations - M. Vamsi Krishna; D. Gowri Sankar (E-Journal of Chemistry)
Simple, rapid and sensitive spectrophotometric procedures were developed for the analysis of Alfuzosin hydrochloride (AFZ) in pure form as well as in pharmaceutical formulations. The methods are based on the reaction of AFZ with nitrite in acid medium to form diazonium ion, which is coupled with ethoxyethylenemaleic ester (Method A) or ethylcyanoacetate (Method B) or acetyl acetone (method C) in basic medium to form azo dyes, showing absorption maxima at 440, 465 and 490 nm respectively. Beer’s law is obeyed in the concentration of 4-20 μg/mL of AFZ for methods A, B and 3-15 μg/mL of AFZ for method C. The molar absorptivity and sandell’s sensitivity of AFZ- ethoxyethylenemaleic ester, AFZ- ethylcyanoacetate and AFZ-acetyl acetone are1.90 × 104, 0.022; 1.93 × 104, 0.021 and 2.67 × 104 L mole-1 cm-1, 0.015 μg cm-2 respectively. The optimum reaction conditions and other analytical parameters were evaluated. The methods were successfully applied to the determination of AFZ in pharmaceutical formulations.